Personal protection equipment for biological hazards: Does it affect tracheal intubation performance?() - Greenland, K.B. (Resuscitation, 2007)
PURPOSE: Personal protection equipment (PPE) is recommended for use during airway management of patients with highly contagious respiratory tract illness. While its use in chemical hazards and its effect on airway management has been assessed previously, there has been no research assessing whether this equipment affects the ability to perform tracheal intubation. It is the intention of this investigation to answer this question. METHODS: Eighteen workers at various level of training were asked to wear three different types of PPE while performing four different types of tracheal intubation. The PPE used included the eye shield, face shield and the “Dustmaster™”. The intubation techniques were direct laryngoscopy, intubation through the intubating laryngeal mask (Fastrach™) and flexible bronchoscopy using the eyepiece and an eyepiece with camera attached. We assessed the time to intubate as well as the incidence of oesophageal intubation. A short questionnaire was used to examine participants’ subjective experiences of wearing the various types of PPE. RESULTS: There was no significant effect on the time to intubation for any of the methods studied. However, all subjects found that the face shield was uncomfortably hot to wear. Fibreoptic bronchoscopic intubation using the eyepiece was particularly difficult with all of the PPE used due to the distance of the subjects’ eye from the eyepiece. CONCLUSION: Although the use of PPE may not affect the length of time to intubate manikins, certain types of PPE may be uncomfortable to wear and noisy. Further research is needed to investigate whether this could be a problem in the clinical setting or in actual difficult intubations.